Culture-Shock Mahasiswa Indonesia di Terengganu Malaysia: Studi Kasus dalam Pembelajaran Balaghah / Culture Shock Experienced by Indonesian Students in Terengganu, Malaysia: A Case Study in Balaghah Learning - Azhar Arij Abiyyah; Khizanatul Hikmah; Abdul Hakim Abdullah (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
The student exchange program between the Faculty of Islamic Studies at Muhammadiyah University of Sidoarjo (UMSIDA) and Sultan Zainal Abidin University (UniSZA) significantly contributes to developing students’ academic and linguistic competencies in cross-cultural learning contexts. This study explores the forms of culture shock experienced by students, their adaptation strategies, and the implications for academic development in Ma’ani Studies. The research approach used is descriptive qualitative with a phenomenological perspective, and data collection techniques include in-depth interviews, participatory observation, and documentation. Findings reveal that students encounter culture shock related to the use of multiple languages, teaching methods, connectivity issues, and classroom dynamics. Adaptation strategies include group discussions, peer tutoring, the use of learning technologies, and institutional support. These strategies facilitate students’ adjustment while enhancing metacognitive awareness, language proficiency, and learning motivation. This adaptation process has implications for increasing students' metacognitive awareness, revitalizing language competencies (Ilmu Ma'ani), increasing intrinsic motivation in learning, and encouraging students to evaluate their learning principles or styles and self-discipline. These findings confirm that the student exchange program is effective in fostering cross-cultural academic readiness and can serve as a foundation for developing more adaptive and systematic policies for similar programs in the future.Program pertukaran mahasiswa antara Fakultas Studi Islam Universitas Muhammadiyah Sidoarjo (UMSIDA) dan Universitas Sultan Zainal Abidin (UniSZA) memberikan kontribusi yang signifikan dalam mengembangkan kompetensi akademik dan linguistik mahasiswa dalam konteks pembelajaran lintas budaya. Penelitian ini mengeksplorasi bentuk-bentuk shock budaya yang dialami mahasiswa, strategi adaptasi mereka, dan implikasi bagi perkembangan akademik dalam Studi Ma’ani. Pendekatan penelitian yang digunakan adalah deskriptif kualitatif dengan perspektif fenomenologis, dan teknik pengumpulan data meliputi wawancara mendalam, observasi partisipatif, dan dokumentasi. Temuan menunjukkan bahwa mahasiswa mengalami kejutan budaya terkait penggunaan bahasa yang beragam, metode pengajaran, masalah konektivitas, dan dinamika kelas. Strategi adaptasi meliputi diskusi kelompok, bimbingan antar teman, penggunaan teknologi pembelajaran, dan dukungan institusional. Strategi-strategi ini memfasilitasi penyesuaian mahasiswa sambil meningkatkan kesadaran metakognitif, kemahiran bahasa, dan motivasi belajar. Proses adaptasi ini memiliki implikasi untuk meningkatkan kesadaran metakognitif mahasiswa, menghidupkan kembali kompetensi bahasa (Imu Ma'ani), meningkatkan motivasi intrinsik dalam belajar, dan mendorong mahasiswa untuk mengevaluasi prinsip atau gaya belajar mereka serta disiplin diri. Temuan ini membuktikan bahwa program pertukaran pelajar efektif dalam meningkatkan kesiapan akademik lintas budaya dan dapat menjadi landasan untuk mengembangkan kebijakan yang lebih adaptif dan sistematis untuk program serupa di masa depan.